The effect of powerlessness on preferences for free-from-products - Zhang, Lijun (Nanyang Technological University, 2022)
Going gluten-free and lactose-free has become popular in the past 10 years ago. However, research has shown that consuming these products can potentially hurt consumers’ health if they do not have allergies conditions. Despite the negative health impact of this dietary preference, little research has examined what drives the increased popularity. The present research explores how the feeling of powerlessness affects preferences for free-from- products (FFPs), defined as products that purposely remove ingredients or materials that cause allergies (e.g., gluten-free, lactose-free). Ten studies provide converging evidence that the feeling of low power increases preferences for FFPs. This preference for FFPs is driven by the powerless individuals’ heightened sensitivity to threat. Consistent with this account, we show that the powerless’ preference for FFPs is attenuated when their sensitivity to threat is lessened: when the powerless are self-affirmed or when the power structure is unstable or illegitimate. We also rule out various alternative explanations, such as status signaling, health-seeking, and impression management accounts. Together, the current research contributes to both the food consumption and power literature by demonstrating experimentally what drives the increasing demand for FFPs and showing how the powerless respond to threat that go beyond social context. This research also provides public policy implications by proposing practical intervention strategies that attenuates the preference for FFPs.